MINAT MAHASANTRI UIN ANTASARI TERHADAP DISKURSUS MODERASI BERAGAMA (STUDI PADA KEGIATAN WAWASAN ISLAM DAN KEBANGSAAN) - Riza Saputra (Jurnal Studi Agama dan Masyarakat, 2021)
Religious moderation is currently one of the most loved courses in the framework of religious harmony. Even now, Ministry of Religion has been launching the Religious Moderation House program in all Islamic religious colleges in Indonesia. This paper discussed the program of activities carried out by Antasari State Islamic University of Banjarmasin to support the government program by instilling the values of religious moderation in all new students. This study applied a qualitative descriptive method with content analysis techniques. The sample in this study were questions posed by Mahasantri during the Islamic and National Insights material every Saturday night at Ma'had Jami'ah UIN Antasari Banjarmasin. The results showed that there were seven themes that most learners’ attraction, namely 1). diversity and tolerance, as many as 91 or 24.53% questions, 2). Synergy and the Importance of Islamic and National Insights, 54 or 14.56% of questions, 3). Radicalism, Terrorism, Fanaticism, 48 or 12.94% questions, 4). Nationalism and Love for the Motherland, 35 or 9.43% of questions, 5). Islamic State and Leaders, 20 or 5.39% of questions, 6). Islamic law in inter-religious relations, 25 or 6.74% questions, and 7). Conflict and Blasphemy, 16 or 4.31% questions. Tolerance and diversity were the most frequently asked questions. Thus, although this lesson carried the theme of Islamic insight and nationalism, this learning tent to be a space for students to ask questions and discuss tolerance which was an important element or part in religious moderation.